Sun dog - Kerbel, Deborah; Del Rizzo, Suzanne (Toronto : Pajama Press, 2018)
"Young Juno the sled dog pup plays on the Arctic tundra with her boy. Under the midnight sun, Juno is too restless to sleep and goes on a nighttime adventure of her own. When she returns to find a polar bear near the door she left open, Juno must summon all her courage to save her boy and send the bear on its way."--